Counting black holes: The cosmic stellar remnant population and implications for LIGO. Issue 1 (2nd August 2017) - Elbert, Oliver D.; Bullock, James S.; Kaplinghat, Manoj
Abstract: We present an empirical approach for interpreting gravitational wave signals of binary black hole mergers under the assumption that the underlying black hole population is sourced by remnants of stellar evolution. Using the observed relationship between galaxy mass and stellar metallicity, we predict the black hole count as a function of galaxy stellar mass. We show, for example, that a galaxy like the Milky Way should host millions of ∼30 M⊙ black holes and dwarf satellite galaxies like Draco should host ∼100 such remnants, with weak dependence on the assumed initial mass function and stellar evolution model. Most low-mass black holes (∼10 M⊙ ) typically reside within massive galaxies ( M ⋆ ≃ 10 11  M⊙ ) while massive black holes (∼50 M⊙ ) typically reside within dwarf galaxies ( M ⋆ ≃ 10 9  M⊙ ) today. If roughly 1 per cent of black holes are involved in a binary black hole merger, then the reported merger rate densities from advanced Laser Interferometer Gravitational-Wave Observatory can be accommodated for a range of merger time-scales, and the detection of mergers with >50 M⊙ black holes should be expected within the next decade. Identifying the host galaxy population of the mergers provides a way to constrain both the binary neutron star or black hole formation efficiencies and the merger time-scale distributions; these events would be primarily localized in dwarf galaxies if the merger time-scale is short compared to the age of the Universe and in massive galaxies otherwise. As more mergers are detected, the prospect of identifying the host galaxy population, either directly through the detection of electromagnetic counterparts of binary neutron star mergers or indirectly through the anisotropy of the events, will become a realistic possibility.